T Cell Tuning for Tumour Therapy: Enhancing Effector Function and Memory Potential of Therapeutic T cells - H. Zech, Mathias; Velica, Pedro; J. Stauss, Hans (Current Gene Therapy, 2015)
The genetic engineering of T cells can lead to enhanced immune-mediated tumour destruction and harbors a great potential for the treatment of cancer. Recent efforts have centered on the design of receptors to re-direct the specificity of T cells towards tumour antigens by means of viral gene transfer. This strategy has shown great success in a number of phase one clinical trials. However, there are still challenges to overcome. On the one hand, T cell function can be further improved to optimize the therapeutic outcome. On the other hand, so called safety switches are required to deal with possible on and off target toxicities. In this review, we will give a brief summary of the success and risks of T cell gene therapy before discussing in detail current strategies to enhance effector function, persistence and safety of adoptively transferred T cells.
Keywords: chimeric antigen receptor